FINANCIAL PERFORMANCE ASSESSMENT OF REGIONAL WATER COMPANY IN KUPANG DISTRICT WITH KEPMENDAGRI APPROACH NO. 47 YEAR 1999 - Deetje Wieske Manuain (P3M- Politeknik Negeri Kupang, 2017)
To be able to control the unfavorable financial condition, it is necessary to control for improvement as necessary. Control within the framework of improvement will be useful if it is based or refers to the company’s financial performance information. From the explanation that has been put forward in the background, it can be formulated the main problem in this research is “How the Company’s Regional Water Finance Performance Kabupaten Kupang with Kepmendagri no. 47 of 1999. The purpose of this research is to know the Financial Performance of Regional Water Company of Kupang Regency with kepmendagri No. 47 year 1999. This research was conducted at Kupang District Water Company, having address at Jalan Anggrek Number: Oepura-Kupang. Data collection technique used is interview technique; is researches do direct question and answer with the leadership of the company especially the financial, observation techniques that researches conduct observation and in-depth examination of financial statement documents to be used as data in the analysis. The technique of data analysis using financial ratios refers to Kepmendagri no. 47 Year 1999 on Performance Appraisal of Regional Water Company. The result of these calculations are further included in the performance classification d” 30, then the financial performance of regional Water Company of Kupang Regency in 2011 in bad / unhealthy condition. The result of analysis of ten indicators of financial performance of kupang district water company shows the company in unhealthy condition or unfavorable performance. With this unhelaty condition indicates a problem in the operational institution of the company. The result showed that the ratio of production assets to water sales by 0.62 with a credit score of 2. This ratio is still considered low and it is an indicator that the production assets have not been able and has not had an effect on the increase in water sales. Based on the result of the previous analysis and discussion, the authors can draw the conclusion that the financial performance of regional water company kupang regency in 2011 in unhealthy conditions. This is caused by several factors, among others : profit is too low, the value of water sales is still low, the company has long-term liabilities with a large enough value, debts abtained are not all used for business capital but others are used to finance operations so that companies can not provide profit. To improve the company’s unhealthy financial condition, the suggestion submitted by the researcher to the company at the end of this writing is: to improve the profitability if the business by increasing the water sales to the customer, minimize the debt value by empowering the accumulated depreciation value so as to reduce the cost burden, debt for investment and not used to pay the company’s operating costs